Redefining Emergency Readiness: Integrating Resilience, Work Engagement, and Situational Awareness in Emergency Care - Maria Claudia; Ferdi Antonio (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Traditional approaches to emergency department readiness in hospitals generally focus on technical factors and rapid response systems. However, non-technical factors such as physicians’ emotional and cognitive readiness in assessing a situation have not received sufficient attention. Therefore, further research is needed on this factor, which also known as situational awareness. This study aims to redefine emergency readiness by examining the role of resilience as a higher-order construct, with medical work engagement and work-life balance. This study deploys a quantitative survey and recruited emergency physicians from private hospitals through purposive sampling, resulting in 213 eligible respondents. Data analysis used a newly disjoint two-stage approach using SEM-PLS due to the measurement of the lower-order construct as the dimensions of resilience that were measured as HOC. The results showed that resilience significantly influenced situational awareness through purpose and direction, and collaborative culture, but not by feeling valued. The strongest influence on situational awareness was found in having a purpose. Work-life balance can significantly strengthen the positive influence of resilience in a collaborative culture. Conversely, work-life balance weakens the influence of situational awarenesson having purpose and direction as well as feeling valued. These findings may have implications for the development of management in emergency care.